2010
DOI: 10.1111/j.1365-2389.2010.01314.x
|View full text |Cite
|
Sign up to set email alerts
|

Soil biodiversity and carbon cycling: a review and synthesis of studies examining diversity–function relationships

Abstract: Biodiversity and carbon (C) cycling have been the focus of much research in recent decades, partly because both change as a result of anthropogenic activities that are likely to continue. Soils are extremely speciesrich and store approximately 80% of global terrestrial C. Soil organisms play a key role in C dynamics and a loss of species through global changes could influence global C dynamics. Here, we synthesize findings from published studies that have manipulated soil species richness and measured the resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
322
3
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 498 publications
(352 citation statements)
references
References 133 publications
22
322
3
5
Order By: Relevance
“…The overall economic benefit of soil biodiversity to ecosystem services, and thus well-functioning soil resources, was estimated to be 1.5 quadrillion U.S. dollars [64]. In recent publications, biodiversity was also shown to influence global C [65] and greenhouse gas budgets [66], enhance water quality [67], moderate soil organic matter decomposition [68,69], regulate nutrient retention and availability [69], and determine the susceptibility of soil to invasion by a pathogen [70]. Synthesis papers by Kremen [71] and Hooper et al [72] have summarized the established linkage between biological communities and ecosystems services, while emphasizing the need to understand biological complexity to properly manage the systems, particularly in agroecosystems.…”
Section: How Does Soil Biology Influence Ecosystem Services That Are mentioning
confidence: 99%
See 1 more Smart Citation
“…The overall economic benefit of soil biodiversity to ecosystem services, and thus well-functioning soil resources, was estimated to be 1.5 quadrillion U.S. dollars [64]. In recent publications, biodiversity was also shown to influence global C [65] and greenhouse gas budgets [66], enhance water quality [67], moderate soil organic matter decomposition [68,69], regulate nutrient retention and availability [69], and determine the susceptibility of soil to invasion by a pathogen [70]. Synthesis papers by Kremen [71] and Hooper et al [72] have summarized the established linkage between biological communities and ecosystems services, while emphasizing the need to understand biological complexity to properly manage the systems, particularly in agroecosystems.…”
Section: How Does Soil Biology Influence Ecosystem Services That Are mentioning
confidence: 99%
“…Agricultural management effects on soil health, in turn, influence the type and magnitude of ecosystem services provided by the soil biota. One measurement of soil health is biodiversity, which has been shown to influence global C [65] and greenhouse gas budgets [66], water quality [67], SOM decomposition [68,69], nutrient retention and availability [69], and the susceptibility of soil to invasion by a pathogen [70]. Many assessments of soil health based on measurements of soil microorganisms have relied on estimates of total biomass and activity.…”
Section: A General Approach: Modify the Whole Soil Communitymentioning
confidence: 99%
“…So a number of authors are of the opinion that there is an excessive amount of specimen in ecosystem, which can perform the same functions (Nannipieri et al, 2003). In this case, after a certain time, which is required for activating species resistant to the impact, the community characteristics aligned with the reference performances (Bowles et al, 2014;Nielsen et al, 2011). At the same time, some publications give evidence in that the loss of some key species may have unexpected effects (Hol et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Mesofauna, primarily fungivores, are well known to be critical links in the nutrient cycle, although studies have found that species richness is more important in low diversity than high diversity faunal communities [48]. A relatively high availability of essential resources, and of biotic richness that may contribute to that availability, could explain why many OG forests tend to remain C sinks despite a buildup of respiratory biomass [49].…”
Section: Differences In Stand Typesmentioning
confidence: 99%